First, transform the equation into standard quadratic form:
#n^2 - color(red)(3n) + color(blue)(18) = 3n - color(red)(3n) - 18 + color(blue)(18)#
#n^2 - 3n + 18 = 0 - 0#
#n^2 - 3n + 18 = 0#
We can now use the quadratic equation to solve this problem:
The quadratic formula states:
For #color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0#, the values of #x# which are the solutions to the equation are given by:
#x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))#
Substituting:
#color(red)(1)# for #color(red)(a)#
#color(blue)(-3)# for #color(blue)(b)#
#color(green)(18)# for #color(green)(c)# gives:
#x = (-color(blue)(-3) +- sqrt(color(blue)((-3))^2 - (4 * color(red)(1) * color(green)(18))))/(2 * color(red)(1))#
#x = (3 +- sqrt(9 - 72))/2#
#x = (3 +- sqrt(-63))/2#